Avoiding cancer risk information. (December 2015) - Emanuel, Amber S.; Kiviniemi, Marc T.; Howell, Jennifer L.; Hay, Jennifer L.; Waters, Erika A.; Orom, Heather; Shepperd, James A.
Abstract: Rationale: Perceived risk for health problems such as cancer is a central construct in many models of health decision making and a target for behavior change interventions. However, some portion of the population actively avoids cancer risk information. The prevalence of, explanations for, and consequences of such avoidance are not well understood. Objective: We examined the prevalence and demographic and psychosocial correlates of cancer risk information avoidance preference in a nationally representative sample. We also examined whether avoidance of cancer risk information corresponds with avoidance of cancer screening. Results: Based on our representative sample, 39% of the population indicated that they agreed or strongly agreed that they would "rather not know [their] chance of getting cancer." This preference was stronger among older participants, female participants, and participants with lower levels of education. Preferring to avoid cancer risk information was stronger among participants who agreed with the beliefs that everything causes cancer, that there's not much one can do to prevent cancer, and that there are too many recommendations to follow. Finally, the preference to avoid cancer risk information was associated with lower levels of screening for colon cancer. Conclusion: These findings suggest that cancer risk information avoidance is a multi-determined phenomenon that is associated with demographic characteristics and psychosocial individual differences and also relates to engagement in cancer screening. Highlights: We examined demographic and psychosocial factors related to cancer risk information avoidance. We also examined whether cancer risk information avoidance was related to cancer screenings. Avoiding cancer risk information was associated with age, gender, and education. Avoiding cancer risk information was also associated with lower levels of screening for colon cancer.